Peptide-based coacervates in therapeutic applications - Ma, Lilusi; Fang, Xiaocui; Wang, Chen (Frontiers in Bioengineering and Biotechnology, 2023)
Coacervates are droplets formed by liquid‒liquid phase separation. An increasing number of studies have reported that coacervates play an important role in living cells, such as in the generation of membraneless organelles, and peptides contribute to condensate droplet formation. Peptides with versatile functional groups and special secondary structures, including α-helices, β-sheets and intrinsically disordered regions, provide novel insights into coacervation, such as biomimetic protocells, neurodegenerative diseases, modulations of signal transmission, and drug delivery systems. In this review, we introduce different types of peptide-based coacervates and the principles of their interactions. Additionally, we summarize the thermodynamic and kinetic mechanisms of peptide-based coacervates and the associated factors, including salt, pH, and temperature, affecting the phase separation process. We illustrate recent studies on modulating the functions of peptide-based coacervates applied in biological diseases. Finally, we propose their promising broad applications and describe the challenges of peptide-based coacervates in the future.